2022
DOI: 10.1021/acsami.2c08047
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Filament Defects in Embedded 3D Printing

Abstract: Embedded 3D printing enables the manufacture of soft, intricate structures. In the technique, a nozzle is embedded into a viscoelastic support bath and extrudes filaments or droplets. While embedded 3D printing expands the printable materials space to low-viscosity fluids, it also presents new challenges. Filament cross-sections can be tall and narrow, have sharp edges, and have rough surfaces. Filaments can also rupture or contract due to capillarity, harming print fidelity. Through digital image analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…When η ink is slightly above η matrix , the printed filaments exhibit the desired circular cross‐section. [ 76 ] When printing lattices, we prioritized the integrity of their nodes by matching η ink ≈ η matrix , even though this results in filaments that are not perfectly round. Our observations are in good agreement with predictions from finite element modelling [ 77 ] as well as our prior heuristics for achieving high fidelity EMB3D printing, which revealed that printable inks must also exhibit G′ values that are less than one order of magnitude higher than the matrix material.…”
Section: Resultsmentioning
confidence: 99%
“…When η ink is slightly above η matrix , the printed filaments exhibit the desired circular cross‐section. [ 76 ] When printing lattices, we prioritized the integrity of their nodes by matching η ink ≈ η matrix , even though this results in filaments that are not perfectly round. Our observations are in good agreement with predictions from finite element modelling [ 77 ] as well as our prior heuristics for achieving high fidelity EMB3D printing, which revealed that printable inks must also exhibit G′ values that are less than one order of magnitude higher than the matrix material.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the final prints look welldefined with smooth surfaces and high shape fidelity, which is often missing in the embedded 3D printing techniques due to a lack of hydrophobicity/hydrophilicity mismatch between the two phases. [8,12,72]…”
Section: Breakup Of Printing Jet Into Dropletsmentioning
confidence: 99%
“…[94] Another system of interest could be solvent segregation driven gel (also known as "SeedGel") with arrested bicontinuous structures, similar to bijels, which could be of potential given their reversibility, reproducibility, tunability of domain sizes, and universality to work with many different types of colloidal particles. [95] Lastly, systematic experimental [72,96,97] and computational simulation [96,98,99] studies on interfacial instabilities have been carried out for embedded 3D printing techniques, but are yet to be explored in the context of associative LL3DP and require attention if these techniques are to be used toward more practical ends. Regardless of the direction for future studies, a major requirement for the success of associative LL3DP techniques is to develop an in-depth understanding of three aspects: a) the components assembled at the liquid-liquid interface at multi-scales (nano-to micro-scale), b) the techniques used for characterizing such assemblies, and c) how the macroscopic properties of the prints are dictated and hence, can be adjusted through these assemblies.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…The rising three-dimensional (3D) printing technique, with its unparalleled freedom to create complex, customized geometries with low cost, shows great promise in controlling the internal morphologies and architectures of cellular materials. Especially, 3D printing of silicones could be realized using direct ink writing (DIW), ,,, inkjet printing, , embedded 3D printing, , vat polymerization, , and expanded techniques for higher resolution. , Mechanical responses of the printed foams could be well predicted, designed, and/or optimized by digital techniques such as simulation and machine learning , and further tailored by controlling the inner structure (such as the polymer network , and filler orientation , ) of the printed filaments. In addition, by introducing micro- or nanoscale pores in the 3D printed filaments using a sacrificial templating concept, a hierarchical porous structure could be achieved, endowing the foam with ultraelasticity (i.e., extreme compressibility and cyclic endurance) and much enhanced active surface area compared to its nonhierarchical counterparts, , which is favorable for high-tech fields such as aerospace, energy, and bioengineering.…”
Section: Introductionmentioning
confidence: 99%
“…6−12 The rising three-dimensional (3D) printing technique, with its unparalleled freedom to create complex, customized geometries with low cost, shows great promise in controlling the internal morphologies and architectures of cellular materials. 6−19 Especially, 3D printing of silicones could be realized using direct ink writing (DIW), 2,6,18,20−22 inkjet printing, 23,24 embedded 3D printing, 7,25 vat polymerization, 26,27 and expanded techniques for higher resolution. 28,29 Mechanical responses of the printed foams could be well predicted, designed, and/or optimized by digital techniques such as simulation and machine learning 2,30 and further tailored by controlling the inner structure (such as the polymer network 31,32 and filler orientation 33,34 ) of the printed filaments.…”
Section: Introductionmentioning
confidence: 99%